2018
DOI: 10.1111/jpn.12987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with Yarrowia lipolytica or Saccharomyces cerevisiae yeast and probiotic additives on growth performance, basic nutrients digestibility and biochemical blood profile in piglets

Abstract: The objective of the study was to compare the efficiency of dietary supplementation of two species of yeast, Yarrowia lipolytica (YL) and Saccharomyces cerevisiae (SC), with or without the addition of a probiotic, on growth performance, basic nutrients digestibility and blood profile in piglets. The experiment was conducted on 360 weaned piglets (180 barrows and 180 gilts). Each treatment comprised 60 piglets. The piglets (27-day-old) were assigned to the following dietary treatments: (a) basal control (C) die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Interest in Yarrowia lipolytica arises from the fact that it grows on the crude glycerol fraction derived from the production of diesel oil [4], so that it constitutes a link between biofuel by-products and animal feed [5]. Studies conducted thus far indicate that the nutritional value of Yarrowia lipolytica makes it suitable for use in animal diets [6,7]. Compared to Saccharomyces cerevisiae, it has a higher content of protein (approx.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in Yarrowia lipolytica arises from the fact that it grows on the crude glycerol fraction derived from the production of diesel oil [4], so that it constitutes a link between biofuel by-products and animal feed [5]. Studies conducted thus far indicate that the nutritional value of Yarrowia lipolytica makes it suitable for use in animal diets [6,7]. Compared to Saccharomyces cerevisiae, it has a higher content of protein (approx.…”
Section: Introductionmentioning
confidence: 99%
“…The current results are in agreement with previous studies that reported the supplementation of yeasts at 30% in fish diets [ 13 ] and at 1.6×107 colony-forming unit/g of nursery diets [ 32 ] reduced the apparent digestibility of nutrients but did not affect the overall growth performance. Conversely, Czech et al [ 33 ] reported that supplementation of 3.0% of Yarrowia lipolytica replacing soybean meal enhanced the growth performance of nursery pigs from 10 to 32 kg. A reduction of nutrient digestibility with 3.0% of Yarrowia lipolytica without affecting the growth performance observed in this study is probably due to the bioactive compounds from yeasts including oleic acid, β-glucans and mannans that play important roles on microbiota modulation and immune system [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are research evidence indicating that the protein of Yarrowia lipolytica growing on industrial glycerol can perfectly complement the protein of wheat, barley and triticale in animal diets, upgrading their protein nutritional value [68]. Previous research using this strain of yeast as a dietary supplement has been carried out on turkeys [41,69,70], piglets [24,71,72], calves [73] and fish such as Atlantic salmon [74,75], Pacific red snapper [76] and Cynoglossus semilaevis [53].…”
Section: Yarrowia Lipolytica As Supplement In Productive Animal Feedmentioning
confidence: 99%
“…In another comparative study, Czech et al [71] investigated the impact of dietary enrichment with Yarrowia lipolytica and S. cerevisiae yeasts with or without the simultaneous use of a probiotic on the performance, basic nutrients digestibility and some biochemical parameters in piglets. The experimental design of this study was the same as the previous work [72].…”
Section: Parametermentioning
confidence: 99%